2018
DOI: 10.1080/03057925.2018.1490889
|View full text |Cite
|
Sign up to set email alerts
|

Forms of support and challenges to developing international-mindedness: a comparative case study within a national and an international school in Turkey

Abstract: This paper uses mixed methods to explore perceptions of international-mindedness within two case study schools in Istanbul, Turkey: a national school with mostly Turkish students and an international school with students from many nationalities. Using a conceptual framework developed by an international education programme, the authors critically analyse pillars of internationalmindedness: multilingualism, intercultural understanding, and global engagement. Findings reveal that the national school was striving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Jackson (2015) found that ‘education abroad’ students did not benefit from their stay in the host environment and experienced few if any gains in intercultural sensitivity. Metli, Martin and Lane (2019) have argued that the development of international mindedness in schools cannot be taken for granted. Similarly, Cause (2009) points out that teachers need to understand that international mindedness will not be developed simply by putting children of different nationalities in the same classroom.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Jackson (2015) found that ‘education abroad’ students did not benefit from their stay in the host environment and experienced few if any gains in intercultural sensitivity. Metli, Martin and Lane (2019) have argued that the development of international mindedness in schools cannot be taken for granted. Similarly, Cause (2009) points out that teachers need to understand that international mindedness will not be developed simply by putting children of different nationalities in the same classroom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Statistical analysis of the results revealed no significant difference between students from the two participating schools. Similarly, the study by Metli (2018) compared national school students to international school students in terms of their development of international mindedness. As with Beek’s findings, there was no statistically significant difference between students enrolled in the national school and international school in terms of their levels of intercultural understanding and global engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations